A huge necrotic liver mass in a 45-year-old woman: delayed hepatic metastasis of a gastrointestinal stromal tumor - Whang, In Yong; Seo, Kyung-Jin; Kim, Hee Yeon; Kim, Chang Wook; Won, Hye Sung (The Korean journal of internal medicine, 2017)
KCI Citation Count: 1